Early Diagnosis of HIV among Infants Born to HIV-Positive Mothers on Option-B Plus in Kampala, Uganda - Jonathan Izudi; Sylvia Auma; John Bosco Alege (AIDS Research and Treatment)
Introduction. Globally, there is delay in accessing early HIV diagnosis (EID) among HIV exposed infants (HEIs). With paucity of data on EID use at Kisenyi Health Center, this study assessed factors associated with EID use among HEIs (HIV exposed infants). Method. This was a cross-sectional study of 246 HIV-positive mother-baby pairs. Data was collected by structured questionnaire, double-entered in EpiData, and analyzed with STATA using multinomial logistic regression at 5% significance level. Results. 132 (53.7%) HEIs were not tested, 60 (24.4%) tested outside EID guideline, and 54 (21.9%) tested per the guideline. Testing per guideline was associated with maternal age above 30 years (AOR = 2.75; 95% CI: 1.20–6.34; P=0.017); testing outside the guideline was associated with maternal HIV serostatus disclosure (AOR = 2.70; 95% CI: 1.10–6.63; P=0.003) and four or more antenatal care (ANC) visits (AOR = 3.25; 95% CI: 1.23–8.59; P=0.017). However, maternal knowledge of HIV transmission was associated with testing outside the guideline (AOR = 2.90; 95% CI: 1.10–7.65; P=0.032) and per the guideline (AOR = 3.70; 95% CI: 1.39–9.88; P=0.009). Conclusion. Timely EID testing was low. Improving maternal knowledge of EID during ANC visits and positive living empowerment is critical.